Demographics and learning styles of adult learners: insights from Kolb’s model - Yoke, Soo Kum; Jamil, Nur Izzah; Ahmad, Siti Noor Dina; Ma’rifatulloh, Sayid; Zuhriyah, Mukminatus (Intelektual Pustaka Media Utama, 2026)
Adult learners have their own learning styles to acquire information and skills. Therefore, this survey study was carried out to determine adult learners’ preferred learning styles based on Kolb’s model and how learner learning style and demographic profile are related. The sample of this study consisted of 39 Indonesian and 32 Malaysian adult learners aged 20 to 54 years old. The instrument used was Kolb’s learning style questionnaire. The questionnaire answers aimed to ascertain which quadrant the students belong to. Meanwhile, the chi-square test for independence was used to determine the relationship between adult learning styles and their demographics. More than half of the participants in this study were found to be reflectors, followed by pragmatists, theorists, and activists. Adult learning styles were also significantly correlated with nationality and educational attainment. However, gender and current employment had no significant relationship with adult learning styles. Expectantly, the results of this present study can be a reference for educators to make learning equally enjoyable and effective for those four types of adult learners.